2019
DOI: 10.1245/s10434-019-07553-y
|View full text |Cite
|
Sign up to set email alerts
|

Is Routine Recurrence Score Testing in Patients Older than 70 Years of Age Warranted? An Evaluation of the National Cancer Database After TAILORx

Abstract: Background. Recurrence score (RS) testing in early-stage, ER-positive breast cancer is used to predict the benefit of adjuvant chemotherapy for disease recurrence and overall survival. TAILORx results decreased the ambiguity of “intermediate risk” RS by creating a binary classification system. We aimed to determine how women ≥ 70 years with intermediate RS were redistributed post-TAILORx and to identify predictors of low RS. Methods. Patients ≥ 70 years with early-stage, node-negative, ER-positive breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Since the development of Oncotype DX RS assay in 2004, RS testing has allowed for a more nuanced understanding of tumor biology and potential benefit from adjuvant chemotherapy in certain patient groups [ 9 ]. It has also led to the reduction of the use of adjuvant chemotherapy as demonstrated in a study by Hassett et al, reporting a 13% decline in the use of chemotherapy between 2006 and 2008 [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the development of Oncotype DX RS assay in 2004, RS testing has allowed for a more nuanced understanding of tumor biology and potential benefit from adjuvant chemotherapy in certain patient groups [ 9 ]. It has also led to the reduction of the use of adjuvant chemotherapy as demonstrated in a study by Hassett et al, reporting a 13% decline in the use of chemotherapy between 2006 and 2008 [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exploratory subgroup analysis showed that while the benefit of adjuvant CT was significant in the subgroup of patients with grade III BC, it was not significant in the grades I-II subgroups. Lee et al concluded that there was a significant correlation between tumor grade and RS; 95% of patients with well-differentiated tumors had low RS, and 56% of patients with poorly/undifferentiated tumors had low RS (25). The interim analysis of the RxPONDER trial, which was presented at the 2020 San Antonio Breast Cancer Symposium, also suggested that adjuvant CT did not benefit postmenopausal patients with ER+, HER2-N1 BC and RS ≤25.…”
Section: Discussionmentioning
confidence: 99%